Analysis of Leading Sector Shifts in Buol District - Dini Aulia Putri; Eko Jokolelono; Rita Yunus; Santi Yunus; Shohib Hakimi (TRANSEKONOMIKA: AKUNTANSI, BISNIS DAN KEUANGAN, 2025)
Buol Regency has had a dynamic economic development since its separation from Tolitoli Regency. However, the non-optimal utilization of sectoral potential and the imbalance of contributions between sectors encourage the need to identify leading sectors as the basis for regional development policies. This study aims to analyze the regional economic structure, identify the basic sectors through Location Quotient analysis, and evaluate sectoral competitiveness with the Shift Share approach during the 2014-2023 period. The analysis methods used include Location Quotient to determine the base/non-base sector and Shift Share to evaluate the growth and competitive advantage of economic sectors. The Location Quotient analysis discover that Buol Regency has a number of economic sectors that have the potential to become leading sectors, such as Agriculture, Forestry and Fisheries; Water Supply; Waste Management, Waste, and Recycling; and other sectors that show Location Quotient (LQ) values greater than 1, indicating a positive contribution to the regional economy. Conversely, sectors with LQ values below 1 (Mining, Processing Industry, Electricity/Gas, Construction, and others) represent non-leading sectors, highlighting development challenges in Buol Regency. Shift Share analysis (2014-2023) reveals no significant economic structural shift, with the economy remaining primarily dependent on agriculture and fisheries despite some positive developments in other sectors. Economic structural shift would typically manifest as increased non-primary sector activity and reduced dependence on natural resource-based sectors. These findings identify priority sectors for regional economic policy. This research uniquely combines two analytical methods to assess sectoral dynamics in Buol—an approach rarely applied in eastern Indonesia's district-level studies.